Decarbonizing the Gulf: Evidence on the Role of Energy Transition, Technological Progress, and Human Capital in Achieving SDG-Aligned Sustainability - Amin, Azka; bte Mohamed Yusoff, Nora Yusma; Arooj, Aqsa; Isik, Cem; Shannak, Sa’d Abdel-Halim; Wanik, Mohd Zamri Che (International Journal of Energy Economics and Policy, 2025)
The energy transition, green growth, technological advancements, and human capital can collectively significantly alleviate carbon dioxide emissions (CO2e) and support long-term sustainable environmental practices. 2030 has been set as the target year by the United Nations for achieving the Sustainable Development Goals (SDGs). As the assessment period approaches, it is essential to understand the progress made by the Gulf Cooperation Council (GCC), given its significant reliance on hydrocarbons. Employing a cross-sectional autoregressive distributed lag (CSARDL) approach, this research investigates the roles of energy transition, green growth, technological innovations, human capital, economic growth, and CO2e in the GCC, utilizing data from 1990 to 2022. The outcomes exhibit that renewable energy, green growth, technological innovations, and human capital significantly contribute to safeguarding the environment in the GCC. On the other hand, nonrenewable energy sources can harm the environment. Regarding policy implications, this research emphasizes the importance of expediting green technological innovations in GCC regions through regulatory measures that promote continuous increases in the implementation of advanced technologies, sustainable energy utilization, and the enhancement of human capital to achieve the SDGs.